Non-Sexual Spooning and Inanimate Affections: Diversifying Intimate Knowledge - de Szegheo-Lang, Naomi (Atlantis, 2015)
This article considers forms of non-normative intimate connection, which have been widely covered by the popular press: stranger intimacies at The Snuggery, a NY business where clients purchase non-sexual cuddling time, as well as objectum-sexuals who are attracted to and/or form intimate relationships with objects. Each case study illuminates the potential in diversifying intimate knowledge, offering pathways to examine socio-cultural constructions of intimacy and drawing on the regulation of affect to challenge dominant modes of relation.